Keterampilan Sosial Peserta Didik Kelas V di Sekolah Dasar GMIT Ende 4 - Siprianus See; Efremtika Osi Lera (Ekspektasi: Jurnal Pendidikan Ekonomi, 2023)
Social skills are a positive potential of the effect aspect that must continue to be possessed and developed by students from an early age. For this reason, this study was carried out with the aim of describing the social skills of grade V students at SDI GMIT Ende 4, in order to be an evaluation material for schools to compile efforts in this case for teachers to be able to optimize school potential. This effort certainly has an impact on the formation of students' social characteristics which can then be translated by students through the implementation of their social skills. The data collection technique in this study was to distribute questionnaires to 51 respondents to be filled in according to their habits and experiences regarding social skills, while the data analysis technique used frequency distribution analysis with the help of SPSS program version 25. The results of this study after the data were analyzed showed that the condition of social skills of grade V students at SDI GMIT Ende 4 tended to be moderate with 43.14% or as many as 22 of 51 class V students who were used as renspondent, and 9.80% or as many as 5 students were in the low category. This means that the condition of social skills of grade V students at SDI GMIT Ende 4 needs to be given good attention with strategic efforts through learning in schools, and teachers must also continue to strive to optimize their roles as facilitators, as triggers, motivators, as supervisors, and as evaluators.